If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x * 9x + 6x + 3 = 6 Reorder the terms for easier multiplication: 9 * 9x * x + 6x + 3 = 6 Multiply 9 * 9 81x * x + 6x + 3 = 6 Multiply x * x 81x2 + 6x + 3 = 6 Reorder the terms: 3 + 6x + 81x2 = 6 Solving 3 + 6x + 81x2 = 6 Solving for variable 'x'. Reorder the terms: 3 + -6 + 6x + 81x2 = 6 + -6 Combine like terms: 3 + -6 = -3 -3 + 6x + 81x2 = 6 + -6 Combine like terms: 6 + -6 = 0 -3 + 6x + 81x2 = 0 Factor out the Greatest Common Factor (GCF), '3'. 3(-1 + 2x + 27x2) = 0 Ignore the factor 3.Subproblem 1
Set the factor '(-1 + 2x + 27x2)' equal to zero and attempt to solve: Simplifying -1 + 2x + 27x2 = 0 Solving -1 + 2x + 27x2 = 0 Begin completing the square. Divide all terms by 27 the coefficient of the squared term: Divide each side by '27'. -0.03703703704 + 0.07407407407x + x2 = 0 Move the constant term to the right: Add '0.03703703704' to each side of the equation. -0.03703703704 + 0.07407407407x + 0.03703703704 + x2 = 0 + 0.03703703704 Reorder the terms: -0.03703703704 + 0.03703703704 + 0.07407407407x + x2 = 0 + 0.03703703704 Combine like terms: -0.03703703704 + 0.03703703704 = 0.00000000000 0.00000000000 + 0.07407407407x + x2 = 0 + 0.03703703704 0.07407407407x + x2 = 0 + 0.03703703704 Combine like terms: 0 + 0.03703703704 = 0.03703703704 0.07407407407x + x2 = 0.03703703704 The x term is 0.07407407407x. Take half its coefficient (0.03703703704). Square it (0.001371742113) and add it to both sides. Add '0.001371742113' to each side of the equation. 0.07407407407x + 0.001371742113 + x2 = 0.03703703704 + 0.001371742113 Reorder the terms: 0.001371742113 + 0.07407407407x + x2 = 0.03703703704 + 0.001371742113 Combine like terms: 0.03703703704 + 0.001371742113 = 0.038408779153 0.001371742113 + 0.07407407407x + x2 = 0.038408779153 Factor a perfect square on the left side: (x + 0.03703703704)(x + 0.03703703704) = 0.038408779153 Calculate the square root of the right side: 0.195981579 Break this problem into two subproblems by setting (x + 0.03703703704) equal to 0.195981579 and -0.195981579.Subproblem 1
x + 0.03703703704 = 0.195981579 Simplifying x + 0.03703703704 = 0.195981579 Reorder the terms: 0.03703703704 + x = 0.195981579 Solving 0.03703703704 + x = 0.195981579 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.03703703704' to each side of the equation. 0.03703703704 + -0.03703703704 + x = 0.195981579 + -0.03703703704 Combine like terms: 0.03703703704 + -0.03703703704 = 0.00000000000 0.00000000000 + x = 0.195981579 + -0.03703703704 x = 0.195981579 + -0.03703703704 Combine like terms: 0.195981579 + -0.03703703704 = 0.15894454196 x = 0.15894454196 Simplifying x = 0.15894454196Subproblem 2
x + 0.03703703704 = -0.195981579 Simplifying x + 0.03703703704 = -0.195981579 Reorder the terms: 0.03703703704 + x = -0.195981579 Solving 0.03703703704 + x = -0.195981579 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.03703703704' to each side of the equation. 0.03703703704 + -0.03703703704 + x = -0.195981579 + -0.03703703704 Combine like terms: 0.03703703704 + -0.03703703704 = 0.00000000000 0.00000000000 + x = -0.195981579 + -0.03703703704 x = -0.195981579 + -0.03703703704 Combine like terms: -0.195981579 + -0.03703703704 = -0.23301861604 x = -0.23301861604 Simplifying x = -0.23301861604Solution
The solution to the problem is based on the solutions from the subproblems. x = {0.15894454196, -0.23301861604}Solution
x = {0.15894454196, -0.23301861604}
| 3/4x-1/3x=6 | | 4-2x=-2+4x | | 3(r-13)=12 | | 5z=z+4 | | 2x=40-3y | | 9a+27=30a | | 11=2q+7 | | -6(-2N-9)=-5(4N-10) | | 360=z+74+78+55 | | 9=8x+x | | y-4=-3(-5)+2 | | 240-x=125 | | 0=z^2-26z+100 | | 6v-v=25 | | 8+4(2x+10)=24 | | 9/26=n/52 | | y=3x^2-30x+69 | | 3n+23=36 | | (5/2)(4x-8)-2(6x-7)=-10 | | 3x+5x-15=6x-1 | | 360=z+55+78+74 | | 25/4=n/12 | | 15x+3=15x-10 | | x^2+10x=4x^2-8 | | 360=2+55+78+74 | | 3b*7n= | | 3x+5x-15=6sx-1 | | 40=((x-0.1)/x)*100 | | x^5-6x^3+9t=0 | | x+1=3x-8 | | x^2+10=4x^2-8 | | 4x-y+15=0 |